Oral L-Dopa Disrupts Behavioral Self-Control in Male Fighting Fish (Betta splendens) - Andrew Velkey; Kate Watson; Nathan White; Abigail Agi; Grace Doebler-Alligood; Isabella Tilmont; Brook Williams Sweeten; Kaitlyn Kinslow (Fishes, 2025)
In their natural habitat, male Betta splendens are territorial resource defenders, whereas females are non-territorial opportunistic foragers. This ecological difference suggests that males may be more capable of delaying gratification for food rewards. The present study examined impulsive choice in Betta splendens through two experiments comparing subjects’ choices between a Smaller-Sooner (SS) reward (1 pellet immediately) and a Larger-Later (LL) reward (3 pellets after 15 s). In Experiment I, the choice distributions of males were more likely to stabilize on the LL option over the SS option, whereas females’ choice distributions were equally likely to stabilize on either option. These findings indicate that most males demonstrated spontaneous behavioral self-control without specialized training, while females were collectively indifferent. Experiment II investigated whether dopamine modulates this behavior by administering oral L-Dopa (60 mg/kg) to males before trials. Using the same procedures, only 30% of L-Dopa-treated males’ choice distributions stabilized on the LL reward, while 70% of experimental males’ choice distributions stabilized on the SS option; the choice distributions of control males were equally likely to stabilize on either reward. These results suggest that elevated dopaminergic activity increases impulsive choice in male Betta splendens. Future studies should examine dopamine agonists and antagonists, as well as female responses, to further clarify dopamine’s role in reward valuation and behavioral self-control in Betta splendens.